A Systematic Literature Review On Learning Media And Realistic Mathematics Education (RME): Classification Of Media Types And RME Characteristics In Enhancing Mathematical Problem-Solving Skills - I Wayan Puja Astawa; I Made Ardana; Ni Wayan Eka Sentana Wati (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
Mathematical problem-solving is a key competency in 21st-century education. Realistic Mathematics Education (RME) emphasizes real-world contexts and has been widely applied to support this skill, alongside the development of various instructional media. This study aims to systematically review the role of RME-based learning media in enhancing students’ mathematical problem-solving skills. Using the PRISMA-guided SLR method, [e.g., 146] articles were identified from Google Scholar and Scopus. After duplicate removal and title–abstract screening, [e.g., 24] full-text articles were assessed, resulting in 12 studies included in the final synthesis. A Systematic Literature Review (SLR) was conducted following the PRISMA protocol. A total of [e.g., 146] articles were initially identified from Google Scholar and Scopus. After duplicate removal and title–abstract screening, [e.g., 24] full-text articles were assessed for eligibility, resulting in 12 studies included in the final synthesis. The analysis was organized into three main categories: (1) types of learning media (digital and non-digital), (2) key characteristics of RME (realistic context, progressive mathematization, and student-centered activities), and (3) impacts on students’ mathematical problem-solving skills. The results indicate that both digital and non-digital RME-based media consistently improve students’ problem-solving abilities.